Ocular morbidity following road traffic acccidents: a retrospective analysis - Das, Shubhra; Bhuyan, Dipak; Addya, Sujit (International Journal Of Community Medicine And Public Health, 2017)
Background: Ocular trauma is a well-known cause of blindness and visual impairment and in industrialised nations it has become the reason for extended hospitalization of ophthalmologic patients. Anually, there are in excess of 2 million cases of ocular trauma, with more than 40,000 individuals sustaining significant visual impairment on a permanent basis. The aim of the present study was to study the pattern of ocular involvement in variety of road traffic accidents, attending the emergency department of Gauhati Medical College and Hospitals; analyse and correlate various factors playing roles in etiology and evaluate the final visual outcome. Methods: The study was conducted at a tertiary care centre in which retrospective analysis of 500 cases, who sustained injury involving any part of eye due to road traffic accidents attending emergency department from 1st January 2014 to 31st December 2016, was performed. Results: The predominant age group was between 21-30 years of age with males (75.2%) dominating over female (24.8%). Lid injury in the form of abrasions, lacerations, oedema to full thickness tear, is the commonest presentation in majority of the studies. RTA is more common in rainy and winter months and during the daytime. Two (2) wheelers is the common type of vehicle involved. Final visual outcome in the present study is good and comparable to other studies. Conclusions: Driving under the influence of alcohol is an important etiology in Northeast India. A significant section of the patients were driving two-wheelers and not following the safety precautions as advised, which calls for rigorous implementation of traffic rules. Last but not the least, it is often said that the prevention is the best way to minimise such unwanted events. Public sensitisation, strict adherence to traffic rules and improved roads are some of the few steps that can go a long way to reduce such events.